Does the Central Bank of the Republic of Turkey Respond Asymmetrically to Inflation and Output?. (November 2019) - Bulut, Umit
This article aims to estimate a forward-looking reaction function for the Central Bank of the Republic of Turkey (CBRT) considering possible asymmetries in the reaction function. For this purpose, it uses quarterly data over the period 2006:1–2018:1 and performs the nonlinear autoregressive distributed lag (NARDL) cointegration test. The findings obtained from the NARDL test indicate that the CBRT has an asymmetric reaction function and considers increases in inflation and decreases in output while adjusting short-term interest rates. Theoretical and practical implications for these findings are also discussed. JEL Classification: C22, E52, E58